Die gesondheidsinligtingsprogram vanaf die skakelkantoor van K.P.A. - H.K. Steyn (AOSIS, 1979)
The organised distribution of health education information material followed up by purposeful personal and community use of the information are the two prerequisites for knowledge about health and health matters. As the fundamental aim of Health Year is to stimulate community involvement in health matters, the Health Year organisation of the Cape Province declared as its primary objectives the above-mentioned two prerequisites. In planning the project it was also necessary to ensure that limited financial resources did not restrict its scope.